BEST PRACTICE IMPLEMENTASI KURIKULUM PADA SEKOLAH ALAM INSAN MULIA (SAIM) SURABAYA - Aji Sofanudin (Balai Penelitian dan Pengembangan Agama Semarang, 2019)
School of nature is a criticism of conventional school implementation through best practice that is different from schools in general. Some of these schools are based on religious values or nuances. Recent development in the management model of nature schools is still not widely studied. This study aims at determining the implementation of curriculum management at this school of nature. This qualitative research uses a case study technique conducted at the Alam Insan Mulia School (SAIM) Surabaya. The results of study suggest that the SAIM curriculum is integrated with nature including: physical nature, contextual learning, and psychological realms. The implementation of its curriculum basically refers to the national curriculum but is done with fun learning. In Kindergarten level, it emphasizes learning through play; in elementary, the curriculum applies the pattern of integrated learning, joyful learning and cooperative learning. While in junior high school, it uses a national curriculum enriched with an international curriculum (Cambridge checkpoint and geographic learning) and senior high school follows a national curriculum enriched with an international-minded curriculum designed to develop an entrepreneurial spirit